No trade-off between growth rate and temperature stress resistance in four insect species. - Isabell Karl; Robby Stoks; Stephanie S Bauerfeind; Anneke Dierks; Kristin Franke; Klaus Fischer (PLoS ONE, 2013)
Although fast growth seems to be generally favored by natural selection, growth rates are rarely maximized in nature. Consequently, fast growth is predicted to carry costs resulting in intrinsic trade-offs. Disentangling such trade-offs is of great ecological importance in order to fully understand the prospects and limitations of growth rate variation. A recent study provided evidence for a hitherto unknown cost of fast growth, namely reduced cold stress resistance. Such relationships could be especially important under climate change. Against this background we here investigate the relationships between individual larval growth rate and adult heat as well as cold stress resistance, using eleven data sets from four different insect species (three butterfly species: Bicyclus anynana, Lycaena tityrus, Pieris napi; one Dipteran species: Protophormia terraenovae). Despite using different species (and partly different populations within species) and an array of experimental manipulations (e.g. different temperatures, photoperiods, feeding regimes, inbreeding levels), we were not able to provide any consistent evidence for trade-offs between fast growth and temperature stress resistance in these four insect species.